Legal Regulation and Protections for The Parties in The Franchise Business Agreements in Indonesia - Hari Sutra Disemadi; Paramita Prananingtyas; Ratna Kumala Sari (Fakultas Hukum Universitas Hang Tuah, 2019)
In Indonesia doing business with the concept of franchising in various fields is currently very popular among the people. Doing business with the concept of franchising is desirable because in addition to being seen in terms of profits and various ease of doing business offered by the franchisor to the franchisee. Franchising is based on an agreement called a franchise agreement, but there are not a few legal problems that arise with the existence of the franchise agreement. Based on this, this research aims to find out the form of arrangement of the franchise agreement and legal protection for the parties in the franchise agreement. The normative juridical method is the method used in this study. This method is intended to analyze the legal materials related to the arrangements in the franchise agreement and legal protection for the parties in Indonesia. This study addresses the franchise business agreements including agreements that are not well-known or innocent and legal protection carried out further regulated in the Republic of Indonesia's Minister of Trade Regulation Number 53/M-DAG/PER/8/2012 regarding Franchising. The legal status of the parties in the franchise agreement in force in Indonesia is independent.